Association of exposure to PM2.5-bound metals with premature rupture of membranes: a prospective cohort study - Liang, Mengdan; Qiu, Liping; Lin, Biyun; Chen, Zhehui; Jiang, Xiannuan; Xie, Mengying; Xie, Xiaowei; Chen, Hanbing; He, Xiongkun; Huang, Xiaoxiao; Lu, Liang; Zhang, Lanlan; et al. (Frontiers in Public Health, 2025)
BackgroundExposure to PM2.5 has been linked to premature rupture of membranes (PROM). However, research on the effects of PM2.5-bound metals on the PROM is limited.MethodsHere, we investigated this relationship using data from 6090 pregnant women, estimating exposure to 11 PM2.5-bound metals throughout pregnancy. Cox models assessed associations between individual metals and PROM, while grouped weighted quantile sum regression (GWQS), quantile g-computation (Q-gcomp), and Bayesian kernel machine regression (BKMR) were used for metal mixtures.ResultsExposure to Al, Cd, Pb, Cr, Ni, Se, and Tl increased PROM risk, with hazard ratios ranging from 1.40 to 1.87. As and Mn were also correlated with PROM during specific trimesters. The GWQS model showed a 3% increased risk of PROM with metal mixture exposure (95% CI: 2%, 4%), mainly driven by Pb in the positive direction. The Q-gcomp model revealed a 5% increased risk (95% CI: 2%, 8%), also primarily due to Pb. In the BKMR model, Ni had the highest influence.ConclusionBoth individual metals and metal mixtures were associated with PROM, with Pb, Se, and Tl positively correlated with preterm PROM.